Econometry Modeling in Analyzing the Determinants of Increasing Life Expectation Rate - Ida Wayan Demung; Made Suyana Utama; Anak Agung Istri Ngurah Marhaeni; I Gusti Wayan Murjana Yasa (International Journal of Social Science and Business, 2022)
Human capital is a term that refers to human self-development in the fields of education, health, and other potentials for increasing productivity. These efforts will be realized if there is awareness, willingness, and ability to live healthily in everyone. This study aimed to analyze the Econometric Model in increasing Life Expectancy with Environmental Sanitation, Health Services, and Immunization Interventions in West Nusa Tenggara. This research was carried out in 10 the Regency/City of West Nusa Tenggara Province, using econometric modeling, namely performing panel data regression with eviews 11 as an analytical tool. The results of econometric modeling found that the life expectancy in West Nusa Tenggara in 2035 was 0.57 months under normal conditions. After intervention with the environmental sanitation variable, the life expectancy in 2035 was 1.08 months, meaning there was an increase of 0.4 months; Health variables, especially delivery assistance carried out by health workers, become the main priority in the model, which can increase life expectancy by 11 months three weeks six days; and the increase in Life Expectancy in West Nusa Tenggara from the aspect of community behavior.